Discovery Learning: Definisi, Sintaksis, Keunggulan dan Kelemahan - Siti Khasinah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
This article aims to provide a simple and clear guidance for school teachers, student-teachers and also in service-teachers in designing lesson plans using Discovery Based Learning. Though there are lots of books, articles, and other sources have discussed the topic, it still be problem for some of those teachers in arranging lesson plan. Based on the writer’s experience in teaching Micro Teaching classes and PPG PAI class, the students seemed to have difficulties in planning the syntaxes of Discovery Learning systematically and set the class activities properly in every syntax. They sometimes, could not able to distinguish the syntaxes of the method from others, even though it is one of the methods suggested and recommended in Curriculum 2013 and have been used widely. To help the students and the teachers, this article supports them with clear definition and the origin of the method, along with its systematic syntaxes, strengths and also weaknesses.